Dental Management of Ectodermal Dysplasia: Two Clinical Case Reports - Somayeh Hekmatfar; Karim Jafari; Raziyeh Meshki; Samaneh Badakhsh (Tabriz University of Medical Sciences, 2012)
Ectodermal dysplasia is a hereditary disorder associated with abnormal development of embryonic ectodermally-derived organs including teeth, nails, hair and sweat glands. Hypodontia of the primary and permanent dentition is the most common oral finding. Therefore, affected patients need dental prosthetic treatments during their developmental years. This report presents two cases of children affected by ectodermal dysplasia with anodontia. Oral rehabilitation was accomplished with removable acrylic prostheses. Treatment had major impacts on self-esteem, masticatory function, speech and facial esthetic.